Seed Borne and Transmission of Bipolaris oryzae, the Causal Pathogen of Brown Spot of Rice - Vu Van Ba; Somsiri Sangchote (Agriculture and Natural Resources, 2006)
Rice brown spot Bipolaris oryzae, in paddy fields was investigated to find the relationship between disease severity on flag leaf and kernel infection, at three growth stages of flowering, milky, and dough stages. Disease incidence and severity of brown spot increased with stage of plant. There was a significant relationship between incidence of infected kernel and severity of infected flag leaf at growth stage 3 of rice; flowering (r = 0.84, P < 0.0001), milky (r = 0.84, P < 0.0001) and dough stage (r = 0.80, P < 0.0001). The transmission of Bipolaris oryzae and location in the seed were studied. Each part of infected kernel including embryo, endosperm, palea, lemma, rachilla, and sterile lemma was found infected by B. oryzae. Rachilla and sterile lemma were shown high level of infection at 82%, 79% respectively. Transmission studies from the infected kernel to the seedling using test tube agar indicated that primary symptom appeared on coleoptile and roots after 7 – 14 days. The first leaf of the seedlings also had symptom after 3 – 4 weeks and some infected seedlings became brown and died at a later stage.